Conception de documents composites, supports de travail des élèves, par des professeurs : obstacles et contraintes d'une pratique enseignante - Stéphanie Quirino Chaves (Nantes Université, 2023)
Composite documents are used by teachers as teaching materials for pupils. Most of the teachers choose to design these documents themselves to make their pupils work. Yet, these materials are both difficult to design and complicated to read and understand. This article focuses on the obstacles that teachers encounter in the context of their documentation work based on the experience of three of them practicing in second year of primary school and having developed three composite documents during their first year of participation in cooperative research group on the continuation of learning to read in cycle 3 (CM1, CM2, 6e). The analysis of these obstacles highlights the necessary evolutions, particularly in terms of teacher training, aimed at making their documentation work effective, at the service of the learning of all pupils.